Neuroprotective and Neurorestorative Processes after Spinal Cord Injury: The Case of the Bulbospinal Respiratory Neurons - Anne Kastner; Valéry Matarazzo (Neural Plasticity)
High cervical spinal cord injuries interrupt the bulbospinal respiratory pathways projecting to the cervical phrenic motoneurons resulting in important respiratory defects. In the case of a lateralized injury that maintains the respiratory drive on the opposite side, a partial recovery of the ipsilateral respiratory function occurs spontaneously over time, as observed in animal models. The rodent respiratory system is therefore a relevant model to investigate the neuroplastic and neuroprotective mechanisms that will trigger such phrenic motoneurons reactivation by supraspinal pathways. Since part of this recovery is dependent on the damaged side of the spinal cord, the present review highlights our current understanding of the anatomical neuroplasticity processes that are developed by the surviving damaged bulbospinal neurons, notably axonal sprouting and rerouting. Such anatomical neuroplasticity relies also on coordinated molecular mechanisms at the level of the axotomized bulbospinal neurons that will promote both neuroprotection and axon growth.